Ancient Egyptian biographies : contexts, forms, functions - Stauder-Porchet, Julie; Frood, Elizabeth; Stauder, Andréas, 1977- (Wilbour studies in Egyptology and Assyriology, 2020)
"(Auto-)biography is a genre of ancient Egyptian written discourse that was central to high culture from its earliest periods. Belonging to the nonroyal elites, these texts present aspects of individual lives and experience, sometimes as narratives of key events, sometimes as characterizations of personal qualities. Egyptian (auto-) biographies offer a unique opportunity to examine the ways in which individuals fashioned distinctive selves for display and the significance of the physical, religious, and social contexts they selected. 0The present volume brings together specialists from a range of relevant periods, approaches, and interests. The studies collected here examine Egyptian (auto-)biographies from a variety of complementary perspectives: (1) anthropological and contrastive perspectives; (2) the original Old Kingdom settings; (3) text format and language; (4) social dimensions; and (5) religious experience"--